Nanocompósitos de matriz polimérica: estratégias de síntese de materiais híbridos - Esteves, ACC (2012)
Associating the well known advantages of hybrid materials to the wide potential of nanomaterials, the new and featuring class of polymer nanocomposites turned into one of the most intensively researched areas. This review highlights recent developments in the field of the synthesis of polymer based nanocomposites. Important issues related to the surface modification of fillers, in order to promote the compatibility between the inorganic/organic components, are also reported. The enhancement of the physical properties and the potential applications of polymer nanocomposites are considered in typical examples, given for each synthetic method described